Electrochemical double layer capacitors containing carbon black additives for improved capacitance and cycle life. (July 2018) - Wang, Yang; Du Pasquier, Aurelien; Li, Derek; Atanassova, Paolina; Sawrey, Scott; Oljaca, Miodrag
Abstract: Carbon black additive, which combines high specific surface area and high purity, was designed to improve gravimetric capacitance and cycle life of electrochemical double layer capacitors. In this study, acid extraction method is employed to remove the impurities in the base carbon black (SC2) and the electrochemical performance of the product materials (SC2A) are evaluated in comparison with other commercially available conductive additives. Results suggest that carbon black with high purity and optimized morphology can not only provide desired electrical conductivity but also improve capacitance and cycle life of the electrochemical cells made with this material. Graphical abstract: Image 1